Implementasi nilai-nilai ketuhanan pancasila pada Q.S As-shaffat dalam kehidupan sehari-hari - rizqulloh, yazid akbar (Maliki Interdisciplinary Journal, 2026)
The COVID-19 pandemic has emerged as a global challenge for various countries, testing the spiritual and social resilience of humanity, including Indonesia as a nation founded on Pancasila. This study examines the relationship between Q.S. As-Saffat verse 4 and the principle of divinity, namely "Belief in the One and Only God," in the context of addressing the COVID-19 pandemic. This verse emphasizes the concept of faith in the One and Only God, which forms the identity of tawhid or the oneness of Allah. The verse reflects that everything that occurs, including the COVID-19 pandemic, is by the will of Allah SWT, compelling us as human beings—especially Muslims—to face this pandemic with the attribute of tawakkal (reliance on God). Through a thematic tafsir (interpretation) approach and an analysis of Pancasila values, this study concludes that the integration of Quranic verses with the principle of divinity can strengthen the spiritual values of Indonesian society, particularly for Muslims. The implications of this approach are relevant as post-pandemic religious policies to build a resilient society based on Quranic values and divinity.